Safety aspects of protease inhibitors for chronic hepatitis C: adverse events and drug-to-drug interactions - Teixeira,Rosângela (2013)
The standard of care therapy of chronic hepatitis C with the combination of pegylated interferon and ribavirin for 24 or 48 weeks was a remarkable accomplishment of the past decade. However, sustained virological responses rates of about 80% (genotypes 2-3) and 50% (geno 3 type 1) were not satisfactory especially for patients infected with genotype 1. Important advances in the biology of HCV have made possible the development of the direct-acting antiviral agents boceprevir and telaprevir with substantial increase in the rates of sustained virological response with shorter duration of therapy for a large number of patients. However, the complexity of triple therapy is higher and several new side effects are expected suggesting greater expertise in the patient management. Anemia and disgeusia are frequent with boceprevir while cutaneous rash, ranging from mild to severe, is expected with telaprevir. Higher risk of drug-drug interactions demand further clinical consideration of the previous well-known adverse events of pegylated interferon and ribavirin. Identification and prompt management of these potential new problems with boceprevir and telaprevir are crucial in clinical practice for optimizing treatment and assuring safety outcomes to HCV-genotype 1 patients.